Legal Analysis of Marriage Agreements After the Constitutional Court Decision Number 69/PUU-xiii/2015 - Munawar Arbiyanto; Wahyudi Wahyudi; Ari Nugroho W.; Agung Setya Nugraha; Dewi Sulisyaningsih (PDIH Untag Semarang, 2025)
This study aims to analyzes changes in the legal status and legal protection of prenuptial agreements before and after Constitutional Court Decision Number 69/PUU-XIII/2015. A comparative approach is used to evaluate the impact of this decision on the regulation of joint property, the rights and obligations of husband and wife, and the legal validation mechanism and legal protection for injured parties. The results show that the Constitutional Court decision expanded freedom of contract by allowing prenuptial agreements to be drawn up during the marriage, thereby strengthening flexibility and legal certainty. Furthermore, the validation mechanism now involves notaries and courts to ensure legality and protection for the weaker party and children. The implications of this decision not only increase justice and gender equality in marriage but also positively impact the business and banking worlds through the separation of personal and joint property. However, challenges such as a lack of publicity and technical guidelines still need to be addressed for this decision to be optimally implemented in family law practice in Indonesia.